Chinese government leaders in Manchukuo, 1931-1937 - Yuan, Jianda, author.
1 online resource.
Keywords: "Drawing on historiography of the Japanese occupation in the Chinese, Japanese, and English languages, this book examines the politics of the Manchukuo puppet state from the angle of notable Chinese who cooperated with the Japanese military and headed its government institutions. Chinese Government Leaders in Manchukuo, 1931-1937 fills a gap in this research and is an ideal resource for scholars studying wartime Asia and Europe, as well as non-specialist readers who are interested in collaboration in general"--